Counter-Monumentality in Indigenous Women’s Literature: A Comparative Analysis of The Black Hill and Wild Swans - Therese, Kulandai (Journal of Educational Research and Policies, 2025)
Memorialisation serves as a crucial space for individuals to express emotions, share stories and find solace in collective grieving. Through literary documentation, this process also fulfils the important function of preserving historical memory by recording significant events, individuals and cultural heritage. However, the act of documenting historical events, especially when left to an authorised few, can lead to the propagation of biased or one-sided narratives. These narratives may uphold certain cultural ideals and values while marginalising others. This ultimately contributes to the dismantling of cultural ideals that do not fit into the dominant narrative. This phenomenon aligns with the concept of “dismantled cultural ideals” (“Enacting Remembrance: Turning Toward Memorializing September 11th” 499) as described by Pivnick. When historical documentation prioritises certain perspectives overs, it can lead to the erasure or distortion of cultural traditions, beliefs and experiences that diverge from the dominant narrative. This selective preservation of history perpetuates power dynamics and exposes existing inequalities within society. These indigenous women writers not only commemorate figures of the past but also celebrate the ordinary family life. Through the act of memorialisation, Dai and Chang reiterate the history of their homeland by making use of the concept of counter-monumentality which may also be referred to as “anti- monumentality” (Stevens et al. 956) to counter the official documentation of their homeland. While some events may be forgotten, others are given importance and considered worthy of memorialising; some emerge to the surface after a long period of submersion.